2006
DOI: 10.1055/s-2006-944525
|View full text |Cite
|
Sign up to set email alerts
|

Charcot Foot in Diabetes: Farewell to the Neurotrophic Theory

Abstract: Neuropathic osteoarthropathy is characterised by relatively painless swelling together with extensive damage in bones and joints, predominantly in the feet and ankles. The uncontrolled natural course of the condition leads to gross foot deformity, skin pressure ulceration, spreading infections, and sometimes amputation. Jean-Martin Charcot in 1883 described "Charcot foot" named after him in patients with tabes dorsalis insensitivity. Charcot believed that intrinsic bone weakness was the underlying condition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 34 publications
(64 reference statements)
2
28
0
3
Order By: Relevance
“…These changes were not compatible with osteomyelitis, being, rather, typical of acute fractures. This point is consistent with a recent review of diabetic foot neuroarthropathy [24]. A study on bone histomorphology showed several pathological findings but did not describe in detail the type of inflammation seen in the 29 cases of osteomyelitis [25].…”
Section: Discussionsupporting
confidence: 86%
“…These changes were not compatible with osteomyelitis, being, rather, typical of acute fractures. This point is consistent with a recent review of diabetic foot neuroarthropathy [24]. A study on bone histomorphology showed several pathological findings but did not describe in detail the type of inflammation seen in the 29 cases of osteomyelitis [25].…”
Section: Discussionsupporting
confidence: 86%
“…Short-term (< 12 months) histomorphological studies in diabetic rats and mice have shown that substitution of insulin deficiency reverses the negative effects that diabetes mellitus has on bone morphology and bone healing [9][10][11][12]21]. Epidemiologic and clinical studies in humans have confirmed that bone quality, in general, is not much affected by diabetes: bone mineral density is slightly reduced in long-standing type 1 diabetes, but normal or increased in type 2 diabetes [8,22]. Diabetic polyneuropathy does not seem to exert negative effects on bone quality and bone healing in diabetic patients; in essence, fracture healing in diabetic polyneuropathy is virtually not different from fracture healing in control subjects [23].…”
Section: Discussionmentioning
confidence: 99%
“…missing warm perception in 87% missing cold perception in 80% Vibration perception threshold n.a. 12 AE 1 Neuropathy symptom score [1][2][3][4][5][6][7][8][9][10] n.a. 6.0 AE 1.…”
Section: Clinical Neuropathy Testingmentioning
confidence: 99%
“…5 In addition, a neurovascular theory suggests a disturbance of sympathetic vascular control leading to hyperemia and exaggerated bone resorption, 2 although this has been debated by others. 6 The exact sequence of events in the development of Charcot foot is unclear, but three etiological causes-neurotrophic, microtraumatic, and neurovascular-may accompany each other depending on the time point of investigation, that is, the duration of the disease and the stage of inflammation. In this context, recent investigations with magnetic resonance imaging (MRI) have demonstrated that an incipient stage of the disease exists, which might be quite different from more chronic stages with long-term inflammation.…”
mentioning
confidence: 99%